Antifungal Activity of Henna Leaf Extract (Lawsonia inermis linn.) Against Inhibition of Trichophyton rubrum Fungal Growth Cause Tinea Unguium - Meutia, Nanda; Putra, Imam Budi; Jusuf, Nelva Karmila (Universitas Muhammadiyah Sumatera Utara, 2021)
Tinea unguium is a common fungal nail infection. Most commonly caused by Trichophyton rubrum. It disturbs not only cosmetic figure, but also but also might have an impact on patients emotional, social and occupational functioning, lastly affecting the overall quality of life. The management of tinea unguium is still challenging. The therapy experienced many failures and recurrences. The aim of this research is to determine the presence of antifungal activity of Lawsonia inermis L. extract and to identify the extract concentration that can inhibit the fungal growth. This research is an experimental in vitro study with isolate from Microbiology Laboratory of Faculty of Medicine, Universitas Sumatera Utara. The Lawsonia inermis L. leaves extracted by maceration method. The antifungal assay was done using dilution method with various concentrations of (3,125%; 6,25%; 12.5%; 25%; 50%; 75% w/v). The mixtures of extract, suspension of Trichophyton rubrum and the media is incubated at 37C for 2-3 days. The mixture was streaked on SDA medium to determine the antifungal activity. The results indicates that Lawsonia inermis L. extracts has an antifungal effect, and with concentrations of 25%, 50% and 75% it can be use to inhibit the growth of Trichophyton rubrum qualitatively in vitro.